2016
DOI: 10.1097/mat.0000000000000415
|View full text |Cite
|
Sign up to set email alerts
|

Severe Thrombocytopenia in Adults with Severe Acute Respiratory Distress Syndrome: Impact of Extracorporeal Membrane Oxygenation Use

Abstract: Extracorporeal membrane oxygenation (ECMO) use is perceived to cause thrombocytopenia (T), but the role of non-ECMO factors in the development of T remains unclear. We sought to evaluate the incidence and factors associated with severe T (platelet count ≤ 50,000/μl) in adults with severe acute respiratory distress syndrome (ARDS) managed with or without ECMO. The ECMO (n = 32) versus the non-ECMO (n = 53) groups had a similar baseline platelet count (214,000 vs. 179,000/μl), Acute Physiology and Chronic Health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
0
9
1
1
Order By: Relevance
“…2). Severe thrombocytopenia was reported only in 6 studies, and its prevalence ranged from 6.3 to 26.6% [8,24,32,35,37,40]. Five studies reported the timeline of platelet count after ECMO start [7,8,16,24,29].…”
Section: • Thrombocytopeniamentioning
confidence: 99%
See 1 more Smart Citation
“…2). Severe thrombocytopenia was reported only in 6 studies, and its prevalence ranged from 6.3 to 26.6% [8,24,32,35,37,40]. Five studies reported the timeline of platelet count after ECMO start [7,8,16,24,29].…”
Section: • Thrombocytopeniamentioning
confidence: 99%
“…The subgroup analysis of thrombocytopenia in V-V ECMO patients included four studies and showed a similar pooled prevalence, 25.4% (95% CI 10.6-61.4; 4 studies), with a high heterogeneity (Fig. 2) [29,32,35,37]. n.a n.a n.a n.a n.a Kalbhenn, 2018 [38] n.a n.a n.a n.a n.a n.a n.a n.a Kimmoun, 2018 [39] n.a Cottini, 2013 [25] n.a n.a Kimmoun, 2018 [39] n.a n.a n.a n.a n.a n.a n.a Ruggeri, 2018 [40] n.a n.a n.a n.a n.a n.a 166/188 (88.3%)…”
Section: • Thrombocytopeniaunclassified
“…Sepsis-induced ARDS has an estimated incidence of over 40% and is the leading cause of ARDS death [21]. ARDS is a life-threatening complication featured by diffuse alveolar damage [22]. The incidence of ARDS varies widely, ranging from 1.5 patients per 100,000 people to nearly 79 patients per 100,000 people; European countries report lower incidence than the United States; mortality also varies due to the severity, age, and underlying medical conditions [23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…As a complex pathological process, ARDS is regulated by transcription factors as well as miRNA. A miRNA is a small endogenous non-coding RNA molecule that includes approximately [18][19][20][21][22][23][24] nucleotides. It usually complements sites in the 3' untranslated region of the target messenger RNA for inhibiting the expression of post-transcriptional gene [8].…”
Section: Introductionmentioning
confidence: 99%
“…Thrombocytopenia is common in patients on ECMO. The degree of thrombocytopenia is not related to the duration of ECMO but rather to the severity of illness and platelet count at the time of cannulation 62,63 . The etiology of platelet dysfunction on ECMO is complex and has not yet been definitively elucidated.…”
Section: Hematologic Complications Of Ecmomentioning
confidence: 99%